The Importance of Anchor Chain Maintenance at MT. Griya Flores - Septianto, Andarum; Saifudin, Iksan (CV. Publikasi Indonesia, 2024)
Anchoring is tying the ship to the bottom of the water so that the ship is not exposed to currents and wind. When anchoring anchors, there are often various kinds of problems stemming from internal and external factors. Internal factors themselves include problems with parts of the anchor that support anchor performance caused by lack of maintenance, especially on the anchor chain. This is what makes the author choose to raise the issue of the role of anchor chain maintenance. The research method used is qualitative descriptive by describing the role of maintaining a good and correct anchor chain. The data used is in the form of primary data obtained through field observations and interviews. Secondary data are obtained through documentation and literature studies. The results showed the need for anchor chain maintenance procedures to support the implementation of PMS on board, to create safe conditions when docking and support anchor work. The impact that will arise if you do not carry out the role of maintaining a good and correct anchor chain, namely corrosion, exhaustion of wildcat gears, influence on the anchor berthing process, the heavy up anchor process is disrupted and can hamper ship operations.